Gemini Sebagai Guru Sunyi (Silent Educator) Tinjauan Sosiologi Pendidikan Atas Pergeseran Otoritas Epistemik Dan Perubahan Pola Sosialisasi Kognitif Siswa - Mobarok, Moh. Ikhsan; Cholichah, Oryza Ummi; Arifin, Zainal (PT. Kreasi Karya Majakata, 2026)
The revolution of Generative Artificial Intelligence (AI), highlighted by the emergence of Large Language Models (LLMs) like Gemini, introduces a disruptive socialization agent into the educational system. This conceptual article, supported by a synthesis of Indonesian Educational Sociology literature, analyzes Gemini as the 'Silent Educator'—a non-human entity that provides instant and non-judgmental knowledge access. The study focuses on two fundamental sociological shifts: First, The Erosion of Epistemic Authority, shifting from the teacher as the validator of legitimate knowledge to an algorithmic authority. Second, The Transformation of Cognitive Socialization Patterns toward a habitus prioritizing digital efficiency, which we term Prompt-Based Habitus. This article argues that mastering the Prompt-Based Habitus risks creating a new digital cultural capital that reinforces existing socioeconomic inequalities, rather than mitigating them. The main implication is the necessity for educators to redefine their role from knowledge transmitters to Ethical Curators and Facilitators of Critical Reflection to prevent epistemic atomization